Kynurenic acid inhibits intestinal hypermotility and xanthine oxidase activity during experimental colon obstruction in dogs - Kaszaki József (NEUROGASTROENTEROLOGY AND MOTILITY, 2008)
Kynurenic acid (KynA), an endogenous antagonist of N-methyl-D-aspartate (NMDA) glutamate receptors, protects the central nervous system in excitotoxic neurological diseases. We hypothesized that the inhibition of enteric glutamate receptors by KynA may influence dysmotility in the gastrointestinal tract. Group 1 of healthy dogs served as the sham-operated control, in group 2, the animals were treated with KynA, while in groups 3 and 4 mechanical colon obstruction was maintained for 7 h. Group 4 was treated with KynA at the onset of ileus. Hemodynamics and motility changes were monitored, and the activities of xanthine oxidoreductase (XOR) and myeloperoxidase (MPO) were determined from tissue samples. Colon obstruction induced a hyperdynamic circulatory reaction, significantly elevated the motility index and increased the mucosal leucocyte accumulation and the XOR activity. The KynA treatment augmented the tone of the colon, permanently decreased the motility index of the giant colonic contractions and reduced the increases in XOR and MPO activities. These effects were concomitant with the in vitroinhibition of XOR activity. In conclusion, KynA antagonizes the obstruction-induced motility responses and XOR activation in the colon. Inhibition of enteric NMDA receptors may provide an option to influence intestinal hypermotility and inflammatory changes.